3 - Le rôle de l'université dans une société africaine en mutation: 10.4314/ad.v26i2.22142 - Mbava , Maweja (Africa Development, 2001)
Inefficiency and isolation are the two major ills affecting the African university today. Inefficiency is illustrated by a mismanagement of allocated resources, lack of sufficient infrastructures, low salaries for teachers, etc., which, in turn, have placed the university in a situation of chronic unrest. As to isolation, the university is completely separated from its environment and the international world. This situation has forced many partners to question the mission of the African University and the efficiency of the activities undertaken by the latter. This article focuses on the state of isolation. It analyses the problems arising from the university's present isolation and describes the role of the latter in bringing about change in African society. It also shows from the American university model how to establish close ties with the society. The work finally encourages cooperation with the international academic world, mainly with the universities of the South.